2015
DOI: 10.1159/000375309
|View full text |Cite
|
Sign up to set email alerts
|

Role of Amyloid from a Multiple Sclerosis Perspective: A Literature Review

Abstract: The traditional concept of multiple sclerosis (MS), that it is primarily a white matter inflammatory disease, has changed a great deal. Thanks to the recent development witnessed in MS research, a whole new idea has emerged that MS is a neurodegenerative disease, and neurodegeneration occurs rather earlier in the pathological process. This has also led to the foundation of the hypothesis that two fundamentally different diseases, Alzheimer's disease (AD) and MS, may share a common mechanism of neurodegeneratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…The ratios increased the classification performance both for people who were falsely classified as positive (by low CSF A β 42) and for people who were falsely classified as negative (by high CSF A β 42). In line with our findings, a positive correlation between the CSF A β 38/A β 42 ratio and cortical amyloid load (assessed with Pittsburgh compound B PET) has been reported in cognitively healthy individuals …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The ratios increased the classification performance both for people who were falsely classified as positive (by low CSF A β 42) and for people who were falsely classified as negative (by high CSF A β 42). In line with our findings, a positive correlation between the CSF A β 38/A β 42 ratio and cortical amyloid load (assessed with Pittsburgh compound B PET) has been reported in cognitively healthy individuals …”
Section: Discussionsupporting
confidence: 92%
“…It might be that subcortical pathologies not specific to AD cause reduced levels of CSF A β 42. Some studies have found low CSF A β 42 levels in multiple system atrophy and multiple sclerosis . In this study, we show that in patients with mild cognitive complaints, low CSF A β 42, A β 40, and A β 38 were all linked to subcortical injury, including increased white matter lesions and enlarged lateral ventricles.…”
Section: Discussionsupporting
confidence: 57%
“…The possibility of using PET imaging with tracers for myelin dynamics in MS patients has also been investigated in recent years. 11 C-1,4-bis(p-Aminostyryl)-2-methoxybenzene (BMB) was the first tracer used for PET imaging of myelin [20]. The tracer shows high affinity for WM, but the its slow kinetics means that a longer acquisition time is required that is not feasible given the short half-life of 11 C (20 min) [20].…”
mentioning
confidence: 99%
“…11 C-1,4-bis(p-Aminostyryl)-2-methoxybenzene (BMB) was the first tracer used for PET imaging of myelin [20]. The tracer shows high affinity for WM, but the its slow kinetics means that a longer acquisition time is required that is not feasible given the short half-life of 11 C (20 min) [20]. Another myelin PET tracer, N-[ 11 C]methyl-4,4′diaminostilbene ( 11 C-MeDAS ), has been evaluated in wildtype and transgenic hypermyelinated mice (Plp-AktDD) [20].…”
mentioning
confidence: 99%
“…When amyloidogenesis involves long polypeptide chains (unlike prions, which tend to be short), the end result is typically a mass of elongated fibrils which disrupt the functioning of otherwise healthy tissue [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%